2015
DOI: 10.1038/srep11715
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbapenem resistance on mortality of patients with Pseudomonas aeruginosa infection: a meta-analysis

Abstract: Treatment of infectious diseases caused by the carbapenem-resistant Pseudomonas aeruginosa (CRPA) is becoming more challenging with each passing year. We conducted a meta-analysis to assess the impact of carbapenem resistance on mortality of patients with P. aeruginosa infection. We searched PUBMED, Web of science, EMBASE, Google Scholar and the Cochrane Library up to December 25, 2014, to identify published cohort or case-control studies. 17 studies, including 6660 patients carrying P. aeruginosa, were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 37 publications
(45 reference statements)
3
39
0
Order By: Relevance
“…This probably will present a particular challenge and could results in a major global problem since carbapenems are the final choice in the treatment of the difficult-to-treat pseudomonal infections and they are often the last resort for treating infections due to multidrug resistant isolates (Nordmann, 2010). The emerging carbapenem resistance will be very dangerous and of serious complications resulting in pan drug resistant strains leading to increased mortality rates (Hong et al, 2015;Liu et al, 2015).In the present study, the resistance rate to imipenem was relatively low and accounted for only 1%. Except for a single isolate which was found to be imipenem resistant with an MIC of 16 µg/ml, all isolates were sensitive to imipenem with MIC of 4 µg/ml, MIC 50 and MIC 90 were equal to 4 µg/ml.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…This probably will present a particular challenge and could results in a major global problem since carbapenems are the final choice in the treatment of the difficult-to-treat pseudomonal infections and they are often the last resort for treating infections due to multidrug resistant isolates (Nordmann, 2010). The emerging carbapenem resistance will be very dangerous and of serious complications resulting in pan drug resistant strains leading to increased mortality rates (Hong et al, 2015;Liu et al, 2015).In the present study, the resistance rate to imipenem was relatively low and accounted for only 1%. Except for a single isolate which was found to be imipenem resistant with an MIC of 16 µg/ml, all isolates were sensitive to imipenem with MIC of 4 µg/ml, MIC 50 and MIC 90 were equal to 4 µg/ml.…”
mentioning
confidence: 75%
“…This probably will present a particular challenge and could results in a major global problem since carbapenems are the final choice in the treatment of the difficult-to-treat pseudomonal infections and they are often the last resort for treating infections due to multidrug resistant isolates (Nordmann, 2010). The emerging carbapenem resistance will be very dangerous and of serious complications resulting in pan drug resistant strains leading to increased mortality rates (Hong et al, 2015;Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, carbapenem resistance in A. baumannii more than doubled between 2003/2005 and 2009/2012 (21.0% to 47.9%) [18]. The high rates of resistance in nonfermenters are of significant concern, as carbapenem resistance is associated with a more than 2-fold increase in mortality for both P. aeruginosa (adjusted OR, 2.38) [19] and Acinetobacter (adjusted OR, 2.49) [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia is a leading cause of death among hospital patients in the United States [21] and is a particular problem in the ICU. The mean hospital stay for P. aeruginosa pneumonia in US ICUs is 55.4 days per patient, and the mortality rate is >20% [22], a frequency that likely increases with carbapenem resistance [19]. These grim statistics highlight the clinical relevance of high Carb-NS rates in respiratory P. aeruginosa isolates and the vital need for more therapeutic options to treat carbapenem-resistant Gram-negative respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a report published in 2002 in Mangalore, India 23 . The emergence of carbapenem resistance is a serious concern 24 . In various studies across the world, varying rates of resistance from 4-60% have been reported for imipenem and meropenem 25 .…”
Section: Figure 4: Distribution Of P Aeruginosa Isolates According Tmentioning
confidence: 99%